The Development of Kyrgyzstan: Integration Processes and Establishment of Customs Unions - Aleksandrowich Bespalov, Dmitij (The Copernicus Journal of Political Studies, 2018)
The author considers the ongoing processes of globalization and division of labor, presented form the perspective of Kyrgyzstan’s economic development. Firstly, he introduced the theoretical background of his study, explaining the significance of economic growth, social stability, and the sustainability of the national economy. Then, he identified the prospects of globalization and integration. In the Kyrgyzstan case study, the author present the structure of Kyrgyz foreign trade and international, economic cooperation, emphasizing the roles of Russian Federation, the People’s Republic of China, and Kazakhstan. It enabled him to inquire about the possible advantages and disadvantages of the future integration of Kyrgyzstan with specialized structures of the Eurasian Economic Community: EurAsEC Customs Union, and the Common Economic Space, which were recognized by the Kyrgyz Government in December 2010, as the main aim of foreign and trade policies. He also compared them to Kyrgyz national interests, paying special attention to bilateral trade balances with Russian, Kazakhstan, and Belarus and to the importance of customs taxes and duties as the state’s revenue sources. The author ends with by concluding that the accession to the Union may seriously affect the Kyrgyz economy. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14761